The effects of cognitive restructuring intervention on state and trait anxiety among Iranian high school students - Motevalli, Saeid; Sulaiman, Tajularipin; Hamzah, Mohd Sahandri Ghani; Garmjani, Maryam Gholampour; Kamaliyeh, Nayereh G.; Roslan, Samsilah (IDOSI Publications, 2013)
The aim of this study was to examine the effects of cognitive restructuringon state and trait anxiety among Iranian high school students. In this study, 94 boy high school students were randomly selected to receive cognitive restructuring through eight psycho-educational sessions. Two-way repeated measure ANOVA indicated that cognitive restructuring has significant effect on trait anxiety symptoms across pre-test,post-test and follow-up. However, the present study found that cognitive restructuringhas not significant effect on students’ state anxiety symptoms across pre-test, post-test and follow-up. Despite these and other limitations, we conclude that cognitive restructuringis effective intervention in order to decrease students’trait anxiety symptoms.